TISSUE ENGINEERING CONSTRUCTIONS USE IN THE TREATMENT OF TROPHIC ULCER DISEASE - Farhod D. Ortiqboyev (Central Asian Journal of Medicine, 2025)
The implementation of new biotechnological analogues (equivalents) of tissues and organs, in particular, human skin equivalents (SE), designed to temporarily or permanently replace damaged or destroyed tissues in trophic ulcer disease, remains an urgent task of regenerative medicine to develop and clinical practice. Currently, there are different types of living cells in the full-layer TE and its individual layers are being created and examined. A comparative analysis of existing SEs at the commercial and clinical pre-trial stage was carried out. The features of their structure and the possibilities of their use in solving experimental and clinical problems were analyzed. The characteristics of the three main variants of SE were considered. Examples of the use of stem cells to create skin equivalents are given. The main advantages of using stem cells as the tissue component of EC are described.